Handbook of Emerging Market Multinational Corporations - Demirbag, Mehmet (Research Handbooks in Business and Management series, 2015)
This Handbook, compiled by leading scholars of international business, focuses on why emerging market multinationals internationalize, how they do so, what advantages they explore and exploit as they internationalize, and what strategies they implement when competing abroad. Collectively, these contributions offer interesting insight into emerging market multinationals' internationalization drivers, growth processes, and expansion behaviour and underscore how these might be similar to and different from the international expansion of developed country internationalizing firms